A Descriptive-Comparative Study on The Status and Level of Implementation of Disaster Risk Reduction and Management Program in Public Elementary Schools of Lingig II District, Surigao Del Sur Division: Perceptions of Teachers and Parents as Basis for A School Improvement Plan - Onsing, Clifford (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study assessed the implementation of the Disaster Risk Reduction and Management (DRRM) Program in public elementary schools in Lingig District, Surigao del Sur, as basis for a proposed School Improvement Plan. Anchored on Ludwig von Bertalanffy’s Systems Theory, the study examined DRRM implementation in terms of disaster prevention and mitigation, disaster preparedness, disaster response, disaster recovery and rehabilitation, safe learning facilities and environment, school DRRM management, and DRRM integration in the curriculum. A quantitative descriptive-comparative research design was employed using adapted survey questionnaires administered to 120 respondents composed of 66 teachers and 54 parents during the School Year 2025–2026. Weighted mean, standard deviation, Independent Samples t-test, One-Way ANOVA, and Pearson Product-Moment Correlation Coefficient were utilized for data analysis. Findings revealed that the overall status of DRRM implementation was “Oftentimes Illustrated,” with disaster preparedness receiving the highest rating, while disaster recovery and rehabilitation obtained the lowest. The overall implementation level of the DRRM Program was “Always Manifested,” particularly in school DRRM management and safe learning facilities and environment. However, curriculum integration, psychosocial support, disaster financing, early warning systems, and long-term rehabilitation planning required further strengthening. Results further showed no significant difference between the perceptions of teachers and parents regarding DRRM implementation, indicating shared recognition of the schools’ strengths and areas needing improvement. The study concluded that public elementary schools in Lingig District generally demonstrated strong DRRM implementation and institutional commitment to disaster preparedness and resilience. It recommended enhancing curriculum integration, strengthening recovery and rehabilitation planning, improving stakeholder collaboration, institutionalizing regular DRRM monitoring, and implementing the proposed School Improvement Plan to address identified gaps. The study supports Sustainable Development Goal (SDG) 4 on Quality Education by promoting safe and resilient learning environments, SDG 11 on Sustainable Cities and Communities through strengthened disaster preparedness, and SDG 13 on Climate Action by enhancing disaster resilience and adaptation strategies in schools. The sustainability impact of the study lies in strengthening educational, institutional, and community resilience through improved DRRM systems, stakeholder collaboration, and evidence-based planning that promote safer and more sustainable school communities.